The Factors Affecting the Performance of Data Fusion Algorithms - Nassar, M.O.; Kanaan, G. (International Conference on Information Management and Engineering: Kuala Lumpur, Malaysia 2009, 2009)
The enormous amount of data which is distributed on the World Wide Web can be very useful if the users became able to get these data in an easy and appropriate method, search engines help the users to find what they need from this enormous amount of data. Meta-search is the application of data fusion to document retrieval, Metasearch engine takes as an input the N ranked lists output by each of N search engines in response to a given query, As output, it computes a single ranked list, which is hopefully an improvement over any input list as measured by standard information retrieval performance metrics such as the mean average precision (MAP). Our goal in this paper is to answer the following question, what are the factors affecting the performance of Data fusion algorithms? The reason behind introducing those factors is the absence of a single source in the literature able to present all those factors in an organized and complete manner. This work is needed to integrate all data fusion performance research findings. This paper contributes to the data fusion literature by two things, firstly; it will deliver all factors affecting the performance of data fusion algorithms in an organized and complete manner. Secondly; it will deliver recommendations which are related to how and when to deal with the factors that affect the performance.